A Multi‐Scale Interface Modeling Study of CNT/rGO Electrode for Lithium‐Oxygen Battery. Issue 9 (2nd March 2022) - Zhang, Tianyu; Li, Jie; Li, Qiang; Zheng, Yang; Yu, Mingfu; Sun, Hong
Abstract: Lithium‐air batteries have high requirements for the structural characteristics and adsorptivity of catalytic electrodes. It is essential to clarify the functions of various materials in catalytic electrodes. In this paper, the mesoscopic mass transfer model and microscopic adsorption model of lithium‐oxygen battery electrodes are developed to study the mass transfer and adsorption process at the interface of the catalytic electrode. Diffusion coefficients, ionic conductivity, radial distribution function, adsorption energy, and charge distribution are analyzed. It is found that the improvement of the graphene mass ratio can promote the diffusion of Li +, oxygen and improve the ionic conductivity of the electrolyte. Meanwhile, graphene has a general absorption capacity for reactants. Adding a small number of carbon nanotubes can effectively enhance the adsorptivity of oxygen. In this way, the high mass transfer efficiency and effective adsorption of reactants required by the catalytic electrode can be met simultaneously. This plays a guiding role in optimizing the catalytic electrode of the lithium‐air battery. Abstract : In this paper, the mass transfer and adsorption at the catalytic interface of lithium‐air battery are analyzed. Mesoscopic dynamics force field for electrolyte of lithium‐air battery was developed. And we found that CNT/RGO composite electrode showed better adsorption capacity.The role of CNT and RGO materials as electrode reaction interface was clarified.